Knowledge, attitudes, and practice toward tuberculosis in high school students in Qingdao, China - Xiaoqi Dai; Shuo Li; Song Song; Meng Chen; Honghong Xu; Xuekui Li; Menghan Zhang; Huaqiang Zhang; Haiyan Sun; Zhongdong Wang (Journal of Infection in Developing Countries)
Introduction: The purpose of this study is to assess the levels of knowledge, attitude, and practice (KAP) related to TB, and to analyze the differences among various demographic groups.